Laboratory manual for anatomy & physiology - Wood, Michael G.; Garrison, Claire W.; Ober, William C. (Pearson, 2013)
"This laboratory manual is designed to serve the lab course that accompanies the two-semester anatomy and physiology lecture course. It provides students with comprehensive coverage of anatomy and physiology, beautiful full-color art and photographs, and an intuitive pedagogical framework. The primary goals of this manual are to provide students with hands-on experiences that reinforce the information they learn in the lecture course and to help them understand three-dimensional relationships, visualize complex structures, and comprehend intricate physiological processes."--p. iii